Role of autophagy in simulated ischemic-reperfused left atrial myocardium. (1st May 2023) - Hermann, Romina; Mestre Cordero, Victoria Evangelina; Fernández Pazos, María de las Mercedes; Reznik, Federico Joaquín; Vélez, Débora Elisabet; Marina Prendes, María Gabriela
Abstract: Background and aim: Autophagy has recently emerged as a potential and promising therapeutic approach to maintain cardiac cellular homeostasis. The aim of the present study was to investigate the role of autophagy in the ischemic-reperfused atrial myocardium. Methods: Isolated rat left atria subjected to simulated ischemia-reperfusion were used. The bathing medium contained either 10 mM d -glucose or 10 mM d -glucose and 1.2 mM palmitate. 3-methyladenine (3-MA) was used as pharmacological autophagy inhibitor. Results: LC3-II/LC3-I ratio, an indicator of autophagosome formation, was significantly enhanced during reperfusion, this increase being slowed by the exposure to high palmitate concentration and prevented by 3-MA. Beclin-1 was significantly increased during reperfusion period in both metabolic conditions, and pharmacological inhibition of AMPK partially prevented LC3-II/LC3-I ratio increase. Autophagy inhibition significantly increased mitochondrial damage and impaired mitochondrial ATP synthesis rate at reperfusion. Tissue ATP content recovery and contractile reserve were also reduced during this period, these effects being more pronounced either in 3-MA treated atria and ischemic-reperfused atria incubated with palmitate. Moreover, severe tachyarrhythmias were observed in the presence of 3-MA, in both metabolic conditions. This phenomenon was partially prevented by mitochondrial inner membrane ion channels blocker, PK11195. Conclusion: Present study provides new insights into the role of autophagy in ischemic-reperfused atrial myocardium. The observation of greater deterioration in mitochondrial structure and function when this process was inhibited, suggests an association between autophagy and the structural and functional preservation of mitochondria. Exogenous metabolic substrates, to which the myocardium is exposed during ischemia-reperfusion, might not affect this process. Highlights: The results support that the autophagic process is induced in atrial myocardium during reperfusion. Autophagy inhibition induces severe mitochondrial damage and spontaneous tachyarrhythmias. ATP synthesis and contractile reserve are impaired by autophagy inhibition. Autophagy activation in atrial myocardium is independent of the exogenous substrates.